A quick look at the 2012 record flood in the Amazon Basin - Satyamurty, Prakki; Costa, Cláudia Priscila Wanzeler da; Manzi, Antônio Ocimar; Cândido, Luiz Antônio (Geophysical Research Letters, 2013)
The water level at the Manaus Port on the Negro River reached its record value of 29.97 m on 29 May 2012. This is higher than the previous record in the year 2009 by 20 cm. The rise of the level from November 2011 till the record maximum is the highest in the past several decades. A cooler South Atlantic and a normal or slightly warmer North Atlantic were associated with a record flood in the Amazon Basin in 2012. The seasonal atmospheric moisture convergence and the precipitation over the Amazon Basin are well correlated. During the period October 2011 through May 2012 the moisture-flux convergence was 38% more intense than climatology. The rainfall equivalence of this excess moisture convergence is about 2.5 mm d-1 in the western Amazon Basin and 1.8 mm d -1 in the whole Amazon Basin. Key Points In May 2012 the Negro River level reached record high value Amazon's convergence was 30% more than its climatological the rainy season La Nina condition produced rainfall in excess in the rainy season in the Amazon ©2013. American Geophysical Union. All Rights Reserved.
Keywords: Amazon Basin; Atmospheric Moisture; Moisture Convergence; North Atlantic; Rainy Seasons; Record Values; River Levels; South Atlantic; Climatology; Moisture; Rain; Water Levels; Floods; Climatology; Flooding; La Nina; Moisture Flux; Rainfall; Seasonality; Water Level; Amazon Basin; Atlantic Ocean; Atlantic Ocean (north); Atlantic Ocean (south); Rio Negro [south America]